LabDuino: An open source tool for science education - Guimaraes Carvalho, Diogo; Castelo Branco Lins, Walquiria (2016 IEEE Frontiers in Education Conference (FIE), 2016)
Research shows that the poor quality of science education and related areas in the Brazilian basic education has been negatively affecting professionals training in research and scientific development, also contributes to high rates of evasion of STEM graduation courses. Also, scientific illiteracy are harmful to society, once it's members losses analytical judgment capability and by that are more influenceable. Therefore, it is necessary to obtain ways to reverse this situation. Inspired by Seymour Papert ideas on constructionism and the maker movement, this paper proposes an opensource embedded tool for science experimentation on K-12 classes. Created over Arduino development board and mounted on a custom circuit board, designed on an open source tool, and embedded on a laser cut box, this tool, called LabDuino, works like an experiment repository, where the student can choose the subject to be explored, then an experiment and run it following instructions, (sensors setup, initial data and so on), presented on the tool's display. The LabDuino is capable to gathering, process, show and optionally store on SD card, up to eight sensors data, promoting a hands-on experience from setting up to experiment execution in a seamless way. It was tested on a Brazilian seventh grade class, where was taught gravity force and it's effects by doing a dropping test, inspired on egg drop experiment. Was observed an increase of 14% on the experiment class grades and a more engaged students by running the experiments.